The Increasing Number of Female Troops in Indonesia’s Peacekeeping Operations: Why Women’s Presence Matters? - Nur Azizah; Hadidah Sallimi; Ainun Dwiyanti (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to shed some light on why Indonesia is committed to increasing the number of female peacekeepers in United Nations Peacekeeping Operations. The analysis of this research used a framework theory of Stephen D. Krasner’s international regime (1980) and the concept of gender mainstreaming. This study analyzed secondary data with a qualitative method and literature research. UN Security Council Resolution 1325 on Women, Peace and Security adopted in 2000 states that gender equality and the full participation of women as active agents in peace and security are necessary. It is driven by the disproportionate impact of armed conflict on women and girls, causing a state of insecurity. In this regard, Indonesia as an active member of the United Nations, is also committed to continuously increasing the participation of female personnel in these operations. The research findings revealed that the ratification of the UN Security Council Resolution 1325 by Indonesia is the main reason why the Indonesian Government is fully committed to increasing the number of female peacekeepers in United Nations Peacekeeping Operations. Resolution 1325, as an international regime, encourages Indonesia to adopt the values of equality and gender mainstreaming, which has implications for the behavior and policies issued by the Indonesian Government, particularly in the UN Peacekeeping Operations. This research also discovered that the number of Indonesian female peacekeepers has been steadily increasing since 2008. Indonesian troops, especially female peacekeepers, have a successful record in peacekeeping missions, as they, along with male peacekeepers, were also awarded service medals for their participation in the MINUSCA operation in August 2021.